PENGARUH AUDIT FEE, AUDIT TENURE, DAN FINANCIAL DISTRESS TERHADAP KUALITAS AUDIT - Wijaya, Natasha; Susilandari, Caecilia Atmini (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This research aims to analyze the influence of audit fees, audit tenure, and financial distress on the audit quality of 30 property, real estate, and construction listed companies on Indonesia Stock Exchange in 2017-2020. Absolute discretionary accruals to detect earnings management are used to proxy audit quality. Audit fees are measured by the total fees paid to the auditor. Audit tenure is measured by total engagement between the auditor and the company. Financial distress is measured by the ratio of debt to equity. The analysis method used Multiple linear regression analysis with SPSS version 25. The result shows that audit fees are positively significant to audit quality. In contrast, audit tenure and financial distress are insignificant to audit quality.